Peran Ecospirituality dalam Etika Lingkungan untuk Menghadapi Krisis Perubahan Iklim - Ainia, Dela Khoirul; Lasiyo, Lasiyo (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The purpose of this research is to understand the role of ecospirituality and environmental ethics in dealing with climate change in Indonesia. This research is conducted qualitatively and the research data is obtained through the collection of news facts, journals and previous research results which are then analysed descriptively interpretative. This research reveals that the current climate change has a correlation with the wrong way humans view nature, thus placing nature and natural resources only as fulfilers of human needs. Some humans today have lost the understanding of morality related to responsibility in managing nature, as a result environmental problems and climate change become a threat to life. The results showed that through ecospirituality and environmental ethics can be one of the strategies that can be applied at the level of individuals and community groups. The role of religious leaders is also influential in making policies on environmental management, because correct and wise environmental management will have an impact on the sustainability of life in the future which can achieve a harmonious balance between humans, nature and God.